Solidification/stabilization of dredged marine sediments for road construction - Wang, Dong Xing (Environmental technology, 2012)
Cement/lime-based solidification is an environmentally sound solution for the management of dredged marine sediments, instead of traditional solutions such as immersion. Based on the mineralogical composition and physical characteristics of Dunkirk sediments, the effects of cement and lime are assessed through Atterberg limits, modified Proctor compaction, unconfined compressive strength and indirect tensile strength tests. The variation of Atterberg limits and the improvement in strength are discussed at different binder contents. The potential of sediments solidified with cement or lime for road construction is evaluated through a proposed methodology from two aspects: I-CBR value and material classification. The test results show the feasibility of solidified dredged sediments for beneficial use as a material in road construction. Cement is superior to lime in terms of strength improvement, and adding 6% cement is an economic and reasonable method to stabilize fine sediments